2019
DOI: 10.1590/0100-29452019495
|View full text |Cite
|
Sign up to set email alerts
|

In vitro germination to overcome dormancy in seeds of ‘Red Globe’, ‘Italia’ and ‘Niagara Rosada’ grapes

Abstract: Dormancy in grape seeds slows the progress of many breeding programs of the crop, culminating in low uniformity and low germination percentages. Conventional methods used to overcome dormancy are time-consuming. Thus, in vitro seed germination emerges as a promising alternative to ensure the germination of grape seeds. In this study, we examined the in vitro germination and vigor of seedlings originating from seeds of ‘Red Globe’, ‘Italia’ and ‘Niagara Rosada’ grapes in growth media supplemented with five conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Grape seeds do not have physical dormancy only. Physiological dormancy has been reported in several studies (Rajasekaran;Vine;Mullins, 1982;Ellis;Hong;Roberts, 1983;Pereira;Terra, 1985;Pommer;Ribeiro, 1988;Conner, 2008;Val;Alvarenga;Cecon, 2010;Generoso et al, 2019). In the work of our group, Generoso et al (2019) proved the existence of physiological dormancy using GA 3 to break it and increase in vitro seed germination of cultivars 'Niágara Rosada', 'Itália' and 'Red Globe '.…”
Section: In Vitro Seed Germinationmentioning
confidence: 68%
See 3 more Smart Citations
“…Grape seeds do not have physical dormancy only. Physiological dormancy has been reported in several studies (Rajasekaran;Vine;Mullins, 1982;Ellis;Hong;Roberts, 1983;Pereira;Terra, 1985;Pommer;Ribeiro, 1988;Conner, 2008;Val;Alvarenga;Cecon, 2010;Generoso et al, 2019). In the work of our group, Generoso et al (2019) proved the existence of physiological dormancy using GA 3 to break it and increase in vitro seed germination of cultivars 'Niágara Rosada', 'Itália' and 'Red Globe '.…”
Section: In Vitro Seed Germinationmentioning
confidence: 68%
“…For cultivars 'Niágara Rosada' (V. labrusca) and Itália' (V. vinifera), the removal of the embryo from the seed and its culture in growth medium provided the highest GSI values (over six) and germination percentages (over 85%) . Generoso et al (2019) worked with the same cultivars and achieved similar germination percentages only when using sectioned seeds and GA 3 in the culture medium, with the result depending on the concentration of GA 3 and the cultivar.…”
Section: In Vitro Germination Of Mature Zygotic Embryosmentioning
confidence: 99%
See 2 more Smart Citations
“…Although seed viability appeared to be high in crosses with ‘Beyaz Çavuş’, germination rates remained very low. Generoso et al (2019) reported that dormancy in grape seeds slows the progress of many breeding programmes of the crop, culminating in low uniformity and low germination percentages.…”
Section: Discussionmentioning
confidence: 99%